(untitled) (De la Crítica, 2023)
The zero point according to S.C. Gómez makes reference to a universal language of science, which does not have a specific point in the map. It is called a no place. It is a neutral observation platform in which the world can be escencially named. It rests on the una tuestinable assumplion of Smith and Hume, human natureis a scope of transcendental foundation which is valid for all peoples in world. Although there is large number of simultaneous companies in the space, they are not necessarily in time. Analytical methad should be used comparing the societies to determine which are in the higher stages and which lower ones in relation to evolutionary scale. Locke claims that, amony contemporary European and american societies there is a non simultaneity relationship